2012
DOI: 10.1111/j.1600-0668.2012.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultraviolet germicidal irradiation and swirling motion on airborneStaphylococcus aureus,Pseudomonas aeruginosaandLegionella pneumophilaunder various relative humidities

Abstract: The studied UV device, with a combination of swirling motion and UVGI, is effective to inactivate airborne S. aureus, P. aeruginosa, and L. pneumophila. This study also explores the factors governing the UVGI and swirling motion against infectious bioaerosols. With understanding the environmental and operational parameters, the studied UV device has the potential to be installed indoors where people are simultaneously present, for example, hospital wards and nursing homes, to prevent the humans from acquiring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
2
24
2
Order By: Relevance
“…2b and S4c). The accumulation of Pseudomonas in the smallest size fraction is in line with the small aerodynamic size (< 1 µm) of common Pseudomonas species (Chang et al, 2013;Möh-ler et al, 2008;Pietsch et al, 2015). Overall, the relative amount of Pseudomonas from all bacteria was highest in the size fraction 1-2.5 µm (Fig.…”
Section: Seasonal Variation and Size Distribution Of Microorganismsmentioning
confidence: 52%
“…2b and S4c). The accumulation of Pseudomonas in the smallest size fraction is in line with the small aerodynamic size (< 1 µm) of common Pseudomonas species (Chang et al, 2013;Möh-ler et al, 2008;Pietsch et al, 2015). Overall, the relative amount of Pseudomonas from all bacteria was highest in the size fraction 1-2.5 µm (Fig.…”
Section: Seasonal Variation and Size Distribution Of Microorganismsmentioning
confidence: 52%
“…Lin and Li reported that a 2-log reduction of nebulized E. coli was achieved by conventional UV lamp (UVGI system) irradiation at 2.4 mJ/cm 2 at 80% RH (26). Also, aerosols of S. aureus were reduced by 3 logs at a dosage of 2,300 mJ/cm 2 with a UVGI system, 30-liter/min airflow, and 87.3 to 90% RH (27). These bacteria are associated with foodborne illness; our results provide a significant baseline of data to help ensure biological food safety in processing.…”
Section: Resultsmentioning
confidence: 99%
“…190 Another potential engineering control that has shown to be effective for other respiratory pathogens is the incorporation of UV germicidal irradiation (UVGI) into indoor air systems for disinfection. 191, 192 Using UV or photocatalytic treatments for disinfection of airborne Legionella has shown some promise; 193, 194 however, fungi might protect bacteria from these types of treatment. 195 In addition to disinfecting the air, it is also important for cooling systems to be regularly cleaned to inhibit biofilm growth.…”
Section: Introductionmentioning
confidence: 99%
“…UV disinfection of airborne bacteria is not an independent factor, as UV disinfection can be affected by relative humidity. 193, 205 Although relative humidity is likely to be the most important environmental factor affecting Legionella survival, for completeness, temperature and solar radiation also merit attention, as results could lead to various engineering controls to prevent legionellosis outbreaks. Finally, we need a more complete understanding of Legionella survival dynamics within aerosols, although as discussed earlier, we first need to understand if we should focus on VBNC or culturable Legionella .…”
Section: Introductionmentioning
confidence: 99%